The benefit of combination therapy depends on disease phenotype and duration in Crohn's disease. Issue 2 (3rd May 2017) - Ananthakrishnan, A. N; Sakuraba, A.; Barnes, E. L.; Pekow, J.; Raffals, L.; Long, M. D.; Sandler, R. S.
Summary: Background: The impact of combination therapy on disease‐related morbidity in patients with established Crohn's disease (CD) or ulcerative colitis (UC) remains to be well‐defined. Aim: To examine the effect of combination therapy on disease outcomes in CD and UC. Methods: Using a multicenter prospective cohort, we classified CD and UC patients as being on monotherapy with anti‐TNF or on combination with an immunomodulator. The primary outcome was a composite of new IBD‐related surgery, hospitalisations, penetrating complications, need for corticosteroids or new biological at 1 year. Multivariable regression models adjusted for potential confounders. Results: We included 707 patients with CD (45% combination therapy) and 164 with UC (38% combination therapy). Combination therapy was not associated with reduction in the composite outcome in either CD (OR: 0.87, 95% CI: 0.63‐1.22) or UC (OR: 1.45, 95% CI: 0.63‐3.38). However, while no difference was noted in those with nonstricturing, nonpenetrating CD, a significant reduction in the likelihood of the outcome was seen in those with stricturing or penetrating CD (30% vs 39%, OR: 0.58, 95% CI: 0.37‐0.90). A stronger effect was also observed in those with disease duration <5 years (OR: 0.35, 95% CI: 0.14‐0.87) compared to those with a longer duration (OR: 0.75, 95% CI: 0.45‐1.27). A similar reduction in occurrence of composite outcome was noted with infliximab and with other anti‐TNF biologics. Conclusion: The benefit of combination immunomodulator‐biological therapy is stronger in those with complicated Crohn's disease, particularly early on in their disease course.